2022
DOI: 10.2807/1560-7917.es.2022.27.39.2200701
|View full text |Cite
|
Sign up to set email alerts
|

Comparing immunogenicity and efficacy of two different mRNA-based COVID-19 vaccines as a fourth dose; six-month follow-up, Israel, 27 December 2021 to 24 July 2022

Abstract: We assess the immunogenicity and efficacy of Spikevax and Comirnaty as fourth dose COVID-19 vaccines. Six months post-fourth-dose, IgG levels were higher than pre-fourth dose at 1.58-fold (95% CI: 1.27–1.97) in Spikevax and 1.16-fold (95% CI: 0.98–1.37) in Comirnaty vaccinees. Nearly 60% (159/274) of vaccinees contracted SARS-CoV-2. Infection hazard ratios (HRs) for Spikevax (0.82; 95% CI: 0.62–1.09) and Comirnaty (0.86; 95% CI: 0.65–1.13) vaccinees were similar, as were substantial-disease HRs, i.e. 0.28 (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Additionally, the fourth dose of the mRNA vaccine correlated with a notable decrease in hospitalisation, symptomatic infection, and severe outcomes during the Omicron predominance period, distinguishing patients from control participants who did not receive a fourth dose 33,37 . These results underscore the effectiveness of both vaccines in elevating IgG levels after the fourth dose and mitigating the risk of Omicron infection and severe disease 32–34,37,38 . Nevertheless, when comparing the monovalent mRNA vaccine (mRNA‐1273 booster) with the bivalent mRNA vaccine (mRNA‐1273.214) after 28 days of the fourth dose, mRNA‐1273.214, as a second booster, exhibited significantly greater neutralising antibody titres against Omicron BA.1 and other variants (BA.4/5, alpha, beta, gamma, and delta), maintaining a safety and reactogenicity profile akin to that of the monovalent vaccine 38 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, the fourth dose of the mRNA vaccine correlated with a notable decrease in hospitalisation, symptomatic infection, and severe outcomes during the Omicron predominance period, distinguishing patients from control participants who did not receive a fourth dose 33,37 . These results underscore the effectiveness of both vaccines in elevating IgG levels after the fourth dose and mitigating the risk of Omicron infection and severe disease 32–34,37,38 . Nevertheless, when comparing the monovalent mRNA vaccine (mRNA‐1273 booster) with the bivalent mRNA vaccine (mRNA‐1273.214) after 28 days of the fourth dose, mRNA‐1273.214, as a second booster, exhibited significantly greater neutralising antibody titres against Omicron BA.1 and other variants (BA.4/5, alpha, beta, gamma, and delta), maintaining a safety and reactogenicity profile akin to that of the monovalent vaccine 38 .…”
Section: Discussionmentioning
confidence: 93%
“…The characteristics of the included studies are summarised in Table 1 32–71 . This systematic review included seven clinical trials, incorporating both randomized and nonrandomised designs; the remaining studies were observational, encompassing cohort, case‒control (test‐negative), and case series studies 32–71 . The most studied vaccines are monovalent messenger RNA (mRNA) vaccines, which include BioNTech nucleoside‐modified messenger RNA (BNT162b2; Pfizer‐BioNTech COVID‐19 vaccine) and Spikevax mRNA‐1273 (Moderna COVID‐19 vaccine).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study in Israel showed that a fourth dose with mRNA1273 caused higher NAbs and anti-RBD levels over time than BNT162b2 [18]. This finding coincided with a slightly higher vaccine efficacy against infection and symptomatic disease with mRNA1273 than BNT162b2 [18,19].…”
Section: Discussionmentioning
confidence: 94%
“… 34 Subsequent studies that were performed in periods when a mix of BA.1, BA.2, BA.4, and BA.5 viruses circulated have reported low effectiveness of a second booster against infection, but higher effectiveness against more severe disease. 18 , 19 , 35 , 36 Waning protection after monovalent boosters and the emergence of antigenically distinct sublineages support the need for bivalent mRNA boosters containing spike protein mRNA of both the original SARS‐CoV‐2 virus and Omicron variant, which are now available in the United States and other countries.…”
Section: Discussionmentioning
confidence: 99%